Manajemen Kasus Penurunan Suhu Tubuh pada Anak dengan Demam Tifus - Uswah Nurkhasanah; Taamu Taamu; Lena Atoy (Health Information : Jurnal Penelitian, 2019)
Typhoid fever is an acute infectious disease that usually affects the digestive tract with symptoms of fever that lasts more than one week, indigestion, and impaired consciousness (Lestari, 2016). Giving a warm compress in the axilla area has a good effect in reducing body temperature in children with fever because that area has large blood vessels. In Indonesia in 2013 the number of typhoid fever sufferers was 9,747 in hospitalized patients (Ministry of Health, 2013). Kendari City Hospital noted that there were 199 cases of typhoid in children in 2016, 234 cases in 2017, and 229 cases in 2018 (Medical Records and SIRS of Kendari City Hospital). Objective: To describe nursing care in children with typhoid fever in decreasing body temperature. Methods: In this study, researchers used a descriptive study, namely a case study. Results: Nursing diagnosis, namely hyperthermia associated with disease. After 3x24 hours of nursing care, the results obtained evaluation of temperature 37.0ºC, pulse 100 times / minute, breathing 20 times / minute, blood pressure 110/70 mmHg, and no increase in skin temperature. Bottom Line: a warm compress can treat an increase in body temperature.